Emotional breakthrough and psychedelics: Validation of the Emotional Breakthrough Inventory. (September 2019) - Roseman, Leor; Haijen, Eline; Idialu-Ikato, Kelvin; Kaelen, Mendel; Watts, Rosalind; Carhart-Harris, Robin
Background: Psychedelic therapy is gaining recognition and the nature of the psychedelic experience itself has been found to mediate subsequent long-term psychological changes. Much emphasis has been placed on the occurrence of mystical-type experiences in determining long-term responses to psychedelics yet here we demonstrate the importance of another component, namely: emotional breakthrough. Methods: Three hundred and seventy-nine participants completed online surveys before and after a planned psychedelic experience. Items pertaining to emotional breakthrough were completed one day after the psychedelic experience, as were items comprising the already validated Mystical Experience Questionnaire and the Challenging Experience Questionnaire. Emotional breakthrough, Mystical Experience Questionnaire and Challenging Experience Questionnaire scores were used to predict changes in well-being (Warwick-Edinburgh Mental Wellbeing Scale) in a subsample of 75 participants with low well-being baseline scores (⩽45). Results: Factor analyses revealed six emotional breakthrough items with high internal consistency (Cronbach's alpha=0.932) and supported our prior hypothesis that emotional breakthrough is a distinct component of the psychedelic experience. Emotional breakthrough scores behaved dose-dependently, and were higher if the psychedelic was taken with therapeutic planning and intent. Emotional breakthrough, Mystical Experience Questionnaire and Challenging Experience Questionnaire scores combined, significantly predicted subsequent changes in well-being ( r =0.45, p =0.0005, n =75), with each scale contributing significant predictive value. Emotional breakthrough and Mystical Experience Questionnaire scores predicted increases in well-being and Challenging Experience Questionnaire scores predicted less increases. Conclusions: Here we validate a six-item 'Emotional Breakthrough Inventory'. Emotional breakthrough is an important and distinct component of the acute psychedelic experience that appears to be a key mediator of subsequent longer-term psychological changes. Implications for psychedelic therapy are discussed.